The effect of land use on phosphorus dynamics in golf course soil - Maja PODGORNIK; Marina PINTAR (Acta Agriculturae Slovenica)
Although, it is usually considered that P applied in fertilizers is taken up by crops or immobilized in the soil, and therefore P losses from agro systems is negligible; recent research indicates that significant P leaching out of the root zone, can occur where certain combinations of land use practice, soil properties and climate condition exist. Therefore special attention was given to dynamics of total P (TP) and plant available P in golf course soils. A field study was carried out to assess how different environmental condition and management practices affect dynamics of TP and plant available P in soil. The proportions of plant available P and TP in the golf rough significantly correlated with precipitation. Since no relationship between precipitation and the P dynamics in soil on the greens and fairways was observed.